Canning of shrimps (Peneaus indicus) in shrimp head extract - Martinez, Lydia O.
This study was conducted to determine the feasibility of canning shrimp in shrimp head extract. The variables were the pretreatment (ascorbic acid dipped and not dippd), and the packing medium (2% brine, shrimp head extract - ascorbic acid mixture and shrimp head extract calamansi juice mixture). The process involved the preparation of shrimp meat by brining, freezing and blanching. Shrimp heads were prepared similarly and the juice extracted. The resulting extract in combination with the specified additives was used as packing medium. The cans exhausted to a center temperature of 180°F, sealed, processed for 10 minutes at 10 pounds pressure (250°F), cooled and stored at room temperature. Both objective and subjective evaluation test results indicated that the canned product packed in shrimp head extract-calamansi juice mixture was the most acceptable. This product had the following characteristics; moderate to characteristic shrimp odor, orange to pinkish-orange sauce, pinkish-orange to orange-pink shrimp meat, tender and whole shrimp meat, and pleasant blend of salt and shrimp flavor. Microbiological test showed negative results for thermophilic flat-sour bacteria and mesophilic bacteria.